2003
DOI: 10.1097/01.tp.0000080881.75767.0e
|View full text |Cite
|
Sign up to set email alerts
|

Importance of hyperglycemia on the primary function of allogeneic islet transplants1

Abstract: This study demonstrates that severe hyperglycemia impairs islet allograft function in BALB/c and NOD mice and that successful islet allotransplantation depends on the degree of hyperglycemia in the recipient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…Thus, the GVA effect is probably minimal in TBI-conditioned recipients given TCD-BM. Second, residual host-type T cells cannot recognize donor-type alloantigen in the MHC-mismatched NOD chimeras in the absence of host-type DCs, because NOD mice were reported to have potent indirect CD4 + T cell response to alloantigens (52). We have observed that in the MHC-mismatched mixed chimeric NOD recipients, the presence of similar percentage of host-type CD4 + T cells did not mediate any rejection either.…”
Section: Discussionmentioning
confidence: 72%
“…Thus, the GVA effect is probably minimal in TBI-conditioned recipients given TCD-BM. Second, residual host-type T cells cannot recognize donor-type alloantigen in the MHC-mismatched NOD chimeras in the absence of host-type DCs, because NOD mice were reported to have potent indirect CD4 + T cell response to alloantigens (52). We have observed that in the MHC-mismatched mixed chimeric NOD recipients, the presence of similar percentage of host-type CD4 + T cells did not mediate any rejection either.…”
Section: Discussionmentioning
confidence: 72%
“…For example, in vitro co-culture experiments have shown that MSCs increase islet viability by upregulating anti-apoptotic genes and improve insulin secretory function by modulating islet ATP content [27]. These effects are likely to be important in the immediate post-transplantation period when improved glycaemic control will favour effective islet engraftment by maintaining function [6,28] and enhancing revascularisation [29]. These factors alone are unlikely to account for the beneficial effects of MSCs in our experiments.…”
Section: Discussionmentioning
confidence: 83%
“…A normoglycaemic environment, in contrast to hyperglycaemia, provides better islet transplantation results [14,17,18] for uncertain reasons that may include enhanced beta cell growth of the grafts [19], and/or avoidance of hyperglycaemia-induced increased oxygen demand with resulting hypoxia, a pro-apoptotic state of beta cells, and less-efficient vascularisation [20,21], although it seems that in the long term, vascular density is unchanged by hyperglycaemia [22]. It cannot be ruled out that nephrectomy leads to release of compensatory growth factors in the contralateral kidney where the 75-islet graft is situated, thus stimulating islet growth [23]; even so, a remarkably low number of islets was required to maintain normoglycaemia.…”
Section: Discussionmentioning
confidence: 99%